Sorry, but that's not correct.
To solve the expression (-3i)(-5i), we can use the fact that i^2 = -1. We can rewrite one of the factors as -5i = 5i^2. Then, we have:
(-3i)(-5i) = -3i * 5i^2
Using the property of exponents, we can multiply the coefficients and combine the i terms:
-3 * 5 * i * i^2 = -15i * i^2
Now, since i^2 = -1, we substitute -1 into the expression:
-15i * -1 = 15i
Therefore, the correct simplified expression is 15i.
i^2 = -1.
(-3i)(-5i) = -3 * -5 * i * i = 15 * i * i
Since i^2 = -1, this becomes:
15 * i * i = 15 * (-1) = -15
Therefore, the correct simplified expression is -15.
1 answer